Peningkatan Pengetahuan Pelajar SMA melalui Sosialisasi dan Edukasi Bahan Tambahan Pangan Berbahaya dalam Jajanan Sekolah di Kota Palu - Diah Ayu Hartini; Bahja Bahja; Ansar Ansar; Siti Hadijah Batjo; Ummu Aiman; Nurulfuadi Nurulfuadi (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
Food Additives (FDA) are certain ingredients added to food to make it look attractive and have a longer shelf life. FDA can be dangerous if used in food in doses greater than the specified standard or consumption limit. Hazardous FDA are usually found in school snacks, so education is needed to increase students' knowledge to protect them from dangerous FDA. The purpose of this community service is to increase students' understanding and knowledge regarding dangerous FDA in school snacks. This activity was carried out at SMA Negeri 7 Palu with a total of 59 participants. The implementation of the activity was in the form of providing education about dangerous FDA in school snacks to students using lecture methods and leaflet distribution. Knowledge measurements were carried out before and after the education. The results of the pre-post test showed that there was an effect of providing education on students' knowledge with a significance value of α = 0.00 with an increase in knowledge of 25.4%. The increase in students' knowledge is expected to have implications for students' attitudes in choosing safe foods for consumption.